2009
DOI: 10.18352/ijc.123
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of upstream and downstream resource managers to engage in compensation schemes for environmental services

Abstract: Providing compensation for land conservation practices adopted by upstream farmers is still an alien concept in the Thai political context. The governance of common-pool natural resources, such as forest and water, has traditionally been under the control of powerful government line agencies, while the contribution of local communities to natural resource conservation have been hardly recognized by policy-makers. Drawing on a case study in Mae Sa watershed, Chiang Mai province, northern Thailand, this paper di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…It implied that the water quality in all of the income levels was an important factor for the choice option of the respondents. This was in line with the previous studies, which showed that the customer placed a high value on maintaining a clean water supply [15][16][17][18][19]. The concern for the water quality of the watershed in the study regions, as well as the lack of significant differences in the MWTA between the upstream and downstream residents, could have been explained by the importance of the drinking water use.…”
Section: A Conditional Logit Model With Two-way Interactionssupporting
confidence: 90%
See 1 more Smart Citation
“…It implied that the water quality in all of the income levels was an important factor for the choice option of the respondents. This was in line with the previous studies, which showed that the customer placed a high value on maintaining a clean water supply [15][16][17][18][19]. The concern for the water quality of the watershed in the study regions, as well as the lack of significant differences in the MWTA between the upstream and downstream residents, could have been explained by the importance of the drinking water use.…”
Section: A Conditional Logit Model With Two-way Interactionssupporting
confidence: 90%
“…Several studies examined the households' preferences of the heterogeneous water attributes [16] and estimated their marginal WTP using CE [17]. Some studies elicited a WTA compensation for the conversion from conventional to environment-friendly agricultural practices, and compared this with the WTP for the water quality [18,19]. However, few studies have investigated the willingness to accept the water quality improvement by providing hypothetical scenarios with several choice sets simultaneously, to both the upstream resource managers and downstream water users.…”
Section: Introductionmentioning
confidence: 99%
“…We also estimated conditional logit models, but the results are similar to the RPL models. In the RPL model, we introduce individual characteristics including age, education, gender, demand for services and income variables including house type and farm size because they can influence the selection of alternative services (Rai and Scarborough, 2013;Sangkapitux et al, 2009). By allowing selected socio-economic variables to interact with the ASC and selected attributes, we identify sources of heterogeneity in decisions.…”
Section: Modeling Household Choices -Cash Versus Labor Contributionsmentioning
confidence: 99%
“…The attributes identified in this experiment were the water quantity, quality, erosion from landslides and cost of the water tariff. A vector of socio-economic variables (s i ), based on linkages with welfare changes and natural resource management [39,40], controlled for household heterogeneity. The socio-economic control variables included were household income, gender, age and drinking water use, and the coefficient (γ) reflected their effects.…”
Section: Empirical Strategy For Estimating Willingness To Paymentioning
confidence: 99%